Total Hip Arthroplasty for Bilateral Femoral Neck Stress Fracture: A Case Report and Review of the Literature - Kevin Moerenhout; Georgios Gkagkalis; G.-Yves Laflamme; Dominique M. Rouleau; Stéphane Leduc; Benoit Benoit (Advances in Orthopedics)
Femoral neck stress fractures (FNSFs) can be treated conservatively or surgically, depending on initial displacement and patient condition. Surgical treatment options include internal fixation, with or without valgus osteotomy or hip arthroplasty, either hemi or total. The latter is mainly considered when initial treatment fails. A review of the literature shows that total hip arthroplasty (THA) is only considered as primary treatment in displaced fractures (type 3) in low-demand patients. We present a case of successive bilateral FNSF in a young active patient, where a THA was performed on one side, after failed internal fixation, and where it was chosen as primary treatment on the other side after failed conservative treatment.